THE ARTISTIC ACTIONS PROTECTING PUBLIC SPACES - Michał Rut (Journal of Civil Engineering, Environment and Architecture, 2022)
The article addresses the issue of participatory art (the so-called political, engaged art), which in its assumptions deals with the subject of marginalized social groups. Such art aims at solving given problems by the diagnosis of a cultural, social and economic situation, by animation actions, media coverage and negotiations between the parties to the conflict. The article specifies the artistic actions which allowed to protect public spaces against the pressure exerted by investors and obliged local governments to conduct restoration work and properly organise places for relaxation and integration of local communities. There is also focus on the experience of Polish artists such as Iza Rutkowska, Julita Wójcik and Joanna Rajkowska as well as the description of the Modraszek Collective action and the selected participatory actions of the project entitled Wrocław – Entrance from the Backyard.